Adaptation of swallowing hyo-laryngeal kinematics is distinct in oral vs. pharyngeal sensory processing - Humbert, Ianessa A. (American Physiological Society, 2012)
Before a bolus is pushed into the pharynx, oral sensory processing is critical for planning movements of the subsequent pharyngeal swallow, including hyoid bone and laryngeal (hyo-laryngeal) kinematics. However, oral and pharyngeal sensory processing for hyo-laryngeal kinematics is not fully understood. In 11 healthy adults, we examined changes in kinematics with sensory adaptation, sensitivity shifting, with oropharyngeal swallows vs. pharyngeal swallows (no oral processing), and with various bolus volumes and tastes. Only pharyngeal swallows showed sensory adaptation (gradual changes in kinematics with repeated exposure to the same bolus). Conversely, only oropharyngeal swallows distinguished volume differences, whereas pharyngeal swallows did not. No taste effects were observed for either swallow type. The hyo-laryngeal kinematics were very similar between oropharyngeal swallows and pharyngeal swallows with a comparable bolus. Sensitivity shifting (changing sensory threshold for a small bolus when it immediately follows several very large boluses) was not observed in pharyngeal or oropharyngeal swallowing. These findings indicate that once oral sensory processing has set a motor program for a specific kind of bolus (i.e., 5 ml water), hyo-laryngeal movements are already highly standardized and optimized, showing no shifting or adaptation regardless of repeated exposure (sensory adaptation) or previous sensory experiences (sensitivity shifting). Also, the oral cavity is highly specialized for differentiating certain properties of a bolus (volume) that might require a specific motor plan to ensure swallowing safety, whereas the pharyngeal cavity does not make the same distinctions. Pharyngeal sensory processing might not be able to adjust motor plans created by the oral cavity once the swallow has already been triggered.